Technical Analysis of the Solar-Assisted Fish Cooling System for Fishing Boat - Risal Amin; Gad Gunawan; Kharis Sugiarto; Happy Aprilia; Samsu Dlukha Nurcholik; Devy Setiorini Sa’adiyah (Indonesian Journal of Maritime Technology, 2026)
As an archipelagic country with a coastline of thousands of kilometers and enormous oceans with high diversity, Indonesia has very rich fishing resources from capture fisheries. But this maritime treasure is typically under-exploited, poorly managed and vulnerable to environmentally damaging activities. Indonesia can implement effective and environmentally friendly technical solutions to prevent marine pollution. For instance, the use of Solar Power equipment (SPS) in fishing vessels can meet the energy needs of the refrigeration equipment on board. The objective of this study is to investigate the viability of solar panel installation on fishing vessels and its effects on vessel stability. The results showed that the vessel's roof is fitted with eight solar panels, each with a capacity of 500 Wp, to create 14.92 kWh per day to power five refrigeration units. Stability analysis shows that the addition of rooftop solar panels, cooling boxes, and batteries in the fish hold is in compliance with IMO Standard A.749(18) Chapter 3, ensuring the safety of the system for practical application.